Investigating the effects of sum-frequency conversions and surface impedance uniformity in traveling wave superconducting parametric amplifiers - Klimovich, N; Wood, S; Day, PK; Tan, B-K (AIP Publishing, 2024)
Traveling wave parametric amplifiers (TWPAs) offer the most promising solution for high gain, broadband, and quantum noise limited amplification at microwave frequencies. Experimental realization of TWPAs has proved challenging with often major discrepancies between the theoretically predicted and the measured gain performance of the devices. Here, we extend the conventional modeling techniques to account for spatial variation in the surface impedance of the thin film and the parametric sum-frequency conversions effect, which subsequently results in accurate reproduction of experimental device behavior. We further show that such an analysis may be critical to ensure fabricated TWPAs can operate as designed.